Crystallization and preliminary X‐ray analysis of a novel haemagglutinin component of the toxin complex of serotype C Clostridium botulinum. Issue 3 (1st March 2014) - Hayashi, Shintaro; Akiyama, Tomonori; Sagane, Yoshimasa; Miyashita, Shin‐Ichiro; Watanabe, Toshihiro; Yajima, Shunsuke; Niwa, Koichi
<x xml:space="preserve">Abstract</x> The botulinum toxin complex, the causative agent of botulism, passes through the intestinal wall via sugar‐chain‐dependent cell binding of a haemagglutinin of 33 kDa molecular weight (HA‐33). The amino‐acid sequence of the C‐terminal half of HA‐33 of the serotype C strain Yoichi (C‐Yoichi) shares only 46% identity with those of the major serotype C strains. Additionally, C‐Yoichi HA‐33 exhibits a unique sugar‐binding specificity. In the present work, C‐Yoichi HA‐33 was expressed in Escherichia coli and crystallized. Diffraction data were collected at a resolution of 2.2 Å. The crystals belonged to space group R3. The complete detailed protein structure will yield insight into how the unique HA‐33 protein recognizes sugar moieties.